P420NAADP signalling augments ischaemia-reperfusion injury via two-pore channel 1 (TPC1). (15th July 2014) - Foote, KK; Zhao, YJ; Graeff, RM; Yellon, DM; Davidson, SM
Abstract: Purpose: Myocardial ischaemia-reperfusion injury (IRI) is characterised by excessive intracellular levels of Ca2+ in cardiomyocytes which leads to mitochondrial pore opening and cell death. Nicotinic acid adenine dinucleotide phosphate (NAADP) is a potent second messenger which mobilises Ca2+ from lysosomes, which in turn can trigger Ca2+ release from the sarcoplasmic reticulum (SR). Lethal Ca2+ oscillations occur in cardiomyocytes during reoxygenation after simulated ischaemia. Ned-19 is a pharmacological inhibitor of NAADP signalling which we found suppresses Ca2+ oscillations during reoxygenation, reducing mitochondrial pore opening and enhancing cell survival. In line with this, we therefore hypothesised that mice with a genetic ablation of the putative NAADP receptor on lysosomes, the two-pore channel (TPC), would be protected against IRI. We also investigated whether the mechanism of protection of Ned-19 involved a direct effect on mitochondria, or on NAADP levels. Methods: Adult TPC1 knockout mice and wild-type littermates were subjected to IRI in vivo by occlusion of the left coronary artery for 30 min followed by 120 min of reperfusion. Infarct size as a proportion of area at risk was measured using triphenyltetrazolium chloride (TTC) staining and Evan's blue. The effect of Ned-19 (10μM) was assessed in cells subject to laser-induced oxidative stress, and in a mitochondrial swelling assay using 500μM free Ca2+ to induce pore opening. NAADP levels were measured in isolated mouse hearts before and after 30 min ischaemia using an enzymatic cycling assay. Results: Mice lacking TPC1 had significantly reduced infarct size compared to wild-type controls (33 ± 5 vs. 51 ± 5%; P<0.05). Ned-19 delayed mPTP opening in cells (100 ± 0 DMSO vs. 155 ± 20% Ned-19; P<0.05), but had no effect on mPTP opening in isolated mitochondria (12 ± 3 vs. 11 ± 2%; P<0.05), supporting an indirect effect involving suppression of Ca2+ oscillations. Myocardial NAADP levels were significantly reduced after a period of 30 min global ischaemia from 8.3 ± 2.0 fmol.mg-1 protein to 2.0 ± 0.3 fmol.mg-1. Upon reperfusion, NAADP levels recovered. Conclusion: These data show that NAADP levels are dynamically regulated during ischaemia and reperfusion supporting a role for NAADP signalling in IRI. NAADP may augment reperfusion injury by stimulating Ca2+ release via TPC1 channels, indirectly augmenting SR Ca2+ oscillations and mitochondrial pore opening. By inhibiting NAADP signalling, Ned-19 may offer a novel approach to preventing IRI.